Clinical Handbook of Insomnia - Attarian, Hrayr P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Expanding on the critical contributions of previous editions, this updated and comprehensive resource covers the latest diagnostic criteria of insomnia. The book is thematically divided into two parts. The first section consists of chapters on nomenclature, epidemiology, pathophysiology, diagnosis and differential diagnosis, complications and prognosis and treatment both pharmacological and behavioral. The second features chapters on insomnia in special populations, including ones on children and adolescents, cancer sufferers and survivors, in pregnancy, in menopausal women and in patients with neurological disorders and those with psychiatric illnesses. This third edition fills an important niche in the medical literature by addressing insomnia in its multiple forms, summarizes the findings published in different medical journals, and presents these to the practicing health care provider in an easily accessible format.
Part 1 Chronic Insomnia Disorder -- Chapter 1 Defining Insomnia -- Chapter 2 Epidemiology of Insomnia -- Chapter 3 Clinical Features, Diagnosis, and Differential Diagnosis -- Chapter 4 Pathophysiology of Insomnia -- Chapter 5 Prognosis and Complications -- Chapter 6 Cognitive Behavioral Therapy for Insomnia -- Chapter 7 Pharmacological Treatment of Insomnia -- Part 2 Insomnia in Special Populations -- Chapter 8 Insomnias of Childhood: Assessment and Treatment -- Chapter 9 Pregnancy-Related Sleep Disturbances and Sleep Disorders -- Chapter 10 Insomnia and Menopause -- Chapter 11 Insomnia in Patients with Comorbid Medical Problems -- Chapter 12 Sleep Disturbance in Cancer Survivors -- Chapter 13 Insomnia in Comorbid Neurological Problems -- Chapter 14 Insomnia in Psychiatric Disorders.
Keywords: Medicine; Neurology; Psychiatry; Behavioral therapy; Medicine & Public Health; Neurology; Psychiatry; Behavioral therapy